Saving disassembly at heavy-duty gas turbine compressor reengineering - Konoplyanchenko, E.; Kolodnenko, V.; Atalawei, W. (НТУ "ХПІ", 2015)
In a paper the considered questions of a machine industry hard loaded responsible products resource saving at a stage of their repair, on an example of the heavy-duty gas-turbine compressors. The main causes of failure and include the results of turbo systems. The modern concept of the rational search path to the failed element of sophisticated equipment. The technique of safe disassembly of their element base in view of maintenance specificity co nditions of and residual influence on an environment is stated. Practical application of the offered approach will allow to increase quality and safety of special assignment, and introduction of the formalized technique in conditions of real manufacture will allow increase in level of efficiency and the use of available means of complex technological equipment.

У статті розглянуті питання збереження ресурсу важко навантажених відповідальних виробів машинобудування на етапі їхнього ремонту, на прикладі газотурбінних компресорів великої потужності. Наведено основні причини та зазначені результати відмов турбокомпресорних установок. Розглянуто сучасні концепції пошуку раціонального шляху доступу до елемента, що відмовив, в складному встаткуванні. Запропоновано методику ощадного розбирання елементної бази газотурбінних компресорів з урахуванням специфіки умов експлуатації та залишкового впливу на навколишнє середовище.
Keywords: repair; selective disassembly; heavy-duty compressors; resource saving; ремонт; часткове розбирання; компресора великої потужності; газові турбіни; збереження ресурсу